2018
DOI: 10.1159/000489885
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibiotic Resistance Determinants and Their Transmissibility among Clinically Isolated Carbapenem-Resistant <b><i>Escherichia coli</i></b> from South India

Abstract: Objectives: The aim of this study was to analyze the prevalence of the CTX-M, TEM, SHV, VIM, NDM, and OXA genes in carbapenemase-producing Escherichia coli and their transmissibility at a tertiary care hospital in south India. Materials and Methods: Twenty-one carbapenem-resistant E. coli (carbapenem-resistant Enterobacteriaceae; CRE) were collected from the Sri Sathya Sai Institute of Higher Medical Sciences (Puttaparthi India). Resistance to antibiotics was analyzed by Vitek-2, and the identity of the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…We found that bla TEM is the most prevalent ESBL among A. baumannii isolates, although previous reports have indicated that bla CTX-M is the pre-dominant ESBL gene [19,20]. Similar findings were observed in our previous report on carbapenem-resistant Enterobacteriaceae [8]. This study suggests that bla SHV is not a commonly encountered ESBL gene among A. baumannii strains on the Indian subcontinent.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that bla TEM is the most prevalent ESBL among A. baumannii isolates, although previous reports have indicated that bla CTX-M is the pre-dominant ESBL gene [19,20]. Similar findings were observed in our previous report on carbapenem-resistant Enterobacteriaceae [8]. This study suggests that bla SHV is not a commonly encountered ESBL gene among A. baumannii strains on the Indian subcontinent.…”
Section: Discussionsupporting
confidence: 88%
“…Genomic analysis of MDR A. baumannii has indicated the presence of integrons, transposons, and other mobile genetic elements (MGEs) such as A. baumannii antibiotic resistance (AbaR) islands. Acquisition of these resistance determinants has been attributed to the potential for horizontal gene transfer among A. baumannii isolates [7, 8]. The ATPase-encoding gene comM (competence protein) is split by the incoming AbaR island, leading to the formation of 2 segments, i.e., comM -AbaR and AbaR- comM [9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Enterobacterales with bla OXA-181 are endemic in the Indian subcontinent (e.g., India, Pakistan, Bangladesh, and Sri Lanka) and are important causes of nosocomial outbreaks in India (175,176) and Bangladesh (177). Nosocomial outbreaks have also been described in Angola (167), South Africa (178), São Tomé and Príncipe (170), and the United Arab Emirates (179) (Fig.…”
Section: Geographical Distribution Of Oxa-181mentioning
confidence: 99%
“…In contrast, Hoang et al [22] isolated strains of E. coli from healthy adults in Vietnam and noted the marked presence of blaCTX-M genes (blaCTX-M-9 and blaCTX-M-1), followed by blaTEM genes. Mahalingam et al [17] analyzed the prevalence and transmissibility of the blaCTX-M, blaTEM, blaSHV, VIM, NDM, and OXA genes in Universitas Scientiarum Vol. 25 (3): 463-488 http://ciencias.javeriana.edu.co/investigacion/universitas-scientiarum carbapenemase-producing E. coli in a tertiary care hospital in Southern India.…”
Section: Amplification Of Genes Linked To Resistance To Antibiotics I...mentioning
confidence: 99%